Film-forming composition, film, circuit sheet, and sensor sheet
By using a coating composition of cycloolefin polymer, physical properties adjusting agent and solvent, the problem that the existing protective layer is prone to deterioration when facing external factors such as water vapor and ultraviolet rays is solved, and efficient protection and weather resistance of circuit sheets and sensor sheets are achieved.
Patent Information
- Application Number
- CN202280006496.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-31
- Filing Date
- 2022-03-29
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-03-29
AI Technical Summary
The protective layer of existing circuit sheets and sensor sheets is prone to deterioration when facing external factors such as water vapor and ultraviolet rays, resulting in a degradation in the performance of the wire or sensor electrodes.
A coating composition containing a cycloolefin polymer, a physical property adjusting agent and a solvent is used to form a transparent, firm coating with excellent protective properties by printing or the like.
It realizes efficient protection of circuit sheets and sensor sheets, improves the transparency, adhesion and weather resistance of the coating, and extends the service life of the protective layer.
Smart Images

Figure CN116323836B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a coating film that can be used as a protective layer or the like of a circuit sheet, a coating film-forming composition for forming the coating film, and a circuit sheet and a sensor sheet having the coating film. Background Art
[0002] The wires arranged in the circuit sheet or the sensor electrodes arranged in the sensor sheet are formed of silver paste containing silver or a transparent conductive polymer called PEDOT / PSS. In order to protect these wires or sensor electrodes from disconnection, corrosion, etc., a highly transparent protective layer covering the surface of the circuit sheet or sensor sheet is provided.
[0003] However, silver paste or transparent conductive polymer is easily degraded by water vapor, ultraviolet rays, etc., and easily vulcanized by sulfur gas, etc. Therefore, it is desired that the protective layer has properties that make these phenomena difficult to occur. The technology of covering the wire with a protective layer is described in, for example, Japanese Patent No. 6167103 (Patent Document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 6167103 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] Due to the demand for lighter, thinner and lower-cost circuit sheets or sensor sheets, it is necessary to reduce the thickness of the protective layer and improve the protective performance.
[0009] Means used to solve problems
[0010] One aspect of the present invention is a film-forming composition having a cycloolefin polymer, a physical property adjusting agent, and a solvent. According to one aspect of the present invention, because the cycloolefin polymer is contained, a film having excellent transparency and firmness can be formed. In addition, because the film-forming composition contains a physical property adjusting agent, the film-forming composition can form a film having improved printability and quality. Moreover, because the film-forming composition contains a solvent, a film can be formed by a method such as printing.
[0011] In one embodiment of the present invention, the film-forming composition is a film having excellent transparency and firmness, wherein the cycloolefin polymer is a cycloolefin ring-opening polymer or a copolymer of a cycloolefin and an olefin. According to one embodiment of the present invention, the cycloolefin polymer is a cycloolefin ring-opening polymer or a copolymer of a cycloolefin and an olefin, and thus the film-forming composition can form a film having excellent transparency and firmness.
[0012] The film-forming composition of one embodiment of the present invention is that the cycloolefin polymer has a polar group on the ring. According to one embodiment of the present invention, the cycloolefin polymer is easily dissolved in a solvent with high polarity. In addition, as a physical property modifier, a material with high polarity can be contained in the film-forming composition at a high concentration.
[0013] In the coating film forming composition according to one embodiment of the present invention, the physical property adjusting agent is at least one of a printability improving agent and a coating film quality improving agent.
[0014] According to one aspect of the present invention, at least one of the printability and the film quality of the film-forming composition can be improved.
[0015] The film-forming composition according to one embodiment of the present invention contains 0.1 to 30% by volume of the physical property adjuster.
[0016] According to one aspect of the present invention, since the physical property adjusting agent is contained in an amount of 0.1 to 30% by volume, the possibility of deterioration of printability and deterioration of coating quality can be avoided.
[0017] In one embodiment of the film-forming composition of the present invention, the physical property adjuster has a polar group selected from a hydroxyl group, an amino group, a carbonyl group, a carboxyl group, a nitro group, a sulfone group, an ester group, an amide group, or a halogen group.
[0018] According to one embodiment of the present invention, since the physical property adjuster has a polar group selected from hydroxyl, amino, carbonyl, carboxyl, nitro, sulfonyl, ester, amide or halogen groups, it can improve the adhesion, bonding or miscibility with respect to the coating object.
[0019] In the film-forming composition according to one embodiment of the present invention, the property adjuster has a reactive functional group selected from an epoxy group, a methacrylic group, a vinyl group, a mercapto group, or an amino group.
[0020] According to one embodiment of the present invention, since the property adjuster has a reactive functional group selected from epoxy, methacrylic, vinyl, mercapto or amino groups, the adhesion of the coating-forming composition to the base sheet or circuit wiring to be coated can be improved.
[0021] A coating film according to one embodiment of the present invention is composed of any of the above-mentioned coating film-forming compositions.
[0022] According to one aspect of the present invention, a coating having excellent transparency, firmness, and coating quality can be realized.
[0023] One embodiment of the present invention is a circuit sheet comprising a base sheet, circuit wiring, and a protective layer composed of a coating film, wherein the coating film is composed of any of the coating film-forming compositions described above.
[0024] According to one embodiment of the present invention, since the coating film composed of any coating film-forming composition is used as a protective layer, a circuit sheet having excellent protection for circuit wiring sandwiched between a base sheet and the protective layer can be formed.
[0025] A circuit sheet according to one embodiment of the present invention has a three-dimensional shape having a curved surface.
[0026] According to one aspect of the present invention, since the circuit sheet has a three-dimensional shape with a curved surface, the circuit sheet can be formed along the space in which the circuit sheet is applied, thereby increasing the degree of freedom in designing a device using the circuit sheet.
[0027] One aspect of the present invention is a sensor sheet including a base sheet, circuit wiring, sensor electrodes, and a protective layer composed of a coating film, wherein the coating film is composed of any of the above-mentioned coating film-forming compositions.
[0028] According to one embodiment of the present invention, the sensor sheet has the coating film formed of any coating film-forming composition as a protective layer, and thus can be formed into a sensor sheet that is excellent in protecting the circuit wiring and sensor electrodes sandwiched between the base sheet and the protective layer.
[0029] A sensor sheet according to one embodiment of the present invention has a three-dimensional shape having a curved surface.
[0030] According to one aspect of the present invention, since the sensor sheet has a three-dimensional shape with a curved surface, the sensor sheet can be formed along a space along which the sensor sheet is applied, thereby increasing the degree of freedom in designing a device using the sensor sheet.
[0031] Effects of the Invention
[0032] According to one aspect of the present invention, a coating film-forming composition having printability can be provided.
[0033] According to one aspect of the present invention, a coating film having excellent protective performance can be provided.
[0034] According to one aspect of the present invention, it is possible to provide a circuit sheet or a sensor sheet having a cover film having excellent protective performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1A , 1B is a schematic diagram of a circuit sheet according to one embodiment of the present invention, Figure 1A is the main view, Figure 1B It is a top view.
[0036] Figure 2A , 2B is a schematic diagram of a sensor sheet according to one embodiment of the present invention, Figure 2A is the main view, Figure 2B It is a top view.
[0037] Figure 3A , 3B is a schematic diagram of a sensor sheet according to another embodiment of the present invention, Figure 3A yes Figure 3B The ⅢA-ⅢA line cross-sectional view, Figure 3B It is a top view. DETAILED DESCRIPTION
[0038] Hereinafter, an example of an embodiment of one mode of the present invention will be described with reference to the drawings. The one mode and the embodiment described below do not unduly limit the contents of the present invention described in the claims, and all the configurations described in the embodiment are not essential to the solution means of the present invention.
[0039] The terms "first" and "second" in this specification and claims are used to distinguish different components and are not used to indicate a specific order or superiority or inferiority, etc. In addition, components that achieve the same effect by a common structure in each embodiment are marked with the same reference numerals and repeated descriptions are omitted.
[0040] <Film-forming composition>
[0041] The film-forming composition described in this embodiment is applied on a substrate sheet such as a circuit sheet or a sensor sheet, and is used as a protective layer for protecting circuit wiring (conducting wire) or sensor electrodes, etc. It has high transparency and high protective performance for the coated object. The film-forming composition contains a cycloolefin polymer, a physical property modifier, and a solvent. The components of the film-forming composition are described below.
[0042] Cycloolefin polymer: When cycloolefin polymer is dissolved in a solvent, it has high cohesive force. If it is used as a coating liquid such as printing ink, it is easy to draw and generally has poor printability. In addition, it has weak adhesion to resin films such as PET as substrate sheets and is easy to peel off. Therefore, although there are cases where cycloolefin polymer is used as a pre-formed plate, it is difficult to say that it is an adhesive resin suitable for printing, etc., and it is a resin that is difficult to use as a coating liquid. However, cycloolefin polymer is amorphous, so it has high transparency and low birefringence. In addition, because it has an alicyclic structure, it has a high glass transition point Tg, and excellent heat resistance and firmness. Moreover, because it has a hydrocarbon structure with few polar groups, it has low hygroscopicity, and it also has excellent light resistance and chemical resistance. Therefore, the inventors have studied what treatment the cycloolefin polymer should be subjected to so that it can be used as an adhesive resin for a coating material.
[0043] Cycloolefin polymers are polymers having an alicyclic structure in the polymer main chain, and examples thereof include COP resins or COC resins obtained by polymerizing cycloolefins. COP resins are cycloolefin ring-opening polymers or hydrogenated products thereof, and examples thereof include norbornene, tetracyclododecene, or derivatives thereof. COC resins are copolymers of cyclic olefins and olefins, i.e., cycloolefin polymers, and examples thereof include copolymers having cyclopentyl residues or substituted cyclopentyl residues inserted into the molecular chain by polymerization of cycloolefins such as norbornene, tetracyclododecene, or derivatives thereof with ethylene or propylene.
[0044] The cycloolefin as the raw material of the cycloolefin polymer can be either monocyclic or polycyclic. In addition, the thermoplastic norbornene resin or the thermoplastic tetracyclododecene resin has excellent adhesion to the substrate sheet or circuit wiring, and does not require high temperature heating when the film-forming composition is coated, and is obtained by drying and curing, so it is preferred. As a thermoplastic norbornene resin, a ring-opening polymer of a norbornene monomer, a hydride thereof, an addition polymer of a norbornene monomer, an addition polymer of a norbornene monomer and an olefin, etc. can be cited. As a thermoplastic tetracyclododecene resin, a ring-opening polymer of a tetracyclododecene monomer, a hydride thereof, an addition polymer of a tetracyclododecene monomer, an addition polymer of a tetracyclododecene monomer and an olefin, etc. can be cited.
[0045] As mentioned above, hydrocarbon structures with few polar groups reduce hygroscopicity. However, as cycloolefin polymers, from the viewpoint of improving adhesion, adhesion, and miscibility, it is a preferred method to use substances with polar groups in the ring. Such cycloolefin polymers with polar groups are preferred in that they have good solubility relative to solvents with high polarity such as ethyl acetate and butyl acetate, and the types and amounts of intermiscible physical property adjusters are also increased. Cycloolefin polymers can have functional groups such as hydroxyl, amino, carbonyl, carboxyl, nitro, sulfonyl, ester, and amide groups. If there are reactive functional groups such as epoxy, methacrylic, vinyl, sulfhydryl, and amino groups, the adhesion of the film-forming composition relative to the substrate sheet or circuit wiring as the coating object can be improved.
[0046] Commercially available products of cycloolefin polymers include, for example, Zeonex (registered trademark; manufactured by Zeon Japan Co., Ltd.), Zeonor (registered trademark; manufactured by Zeon Japan Co., Ltd.), and Arton (registered trademark; manufactured by JSR Corporation) for COP resins. In addition, Apel (registered trademark; manufactured by Mitsui Chemicals, Inc.) and Topas (registered trademark; manufactured by Polyplastics Co., Ltd.) for COC resins can be cited.
[0047] The amount of cycloolefin polymer is 5 to 70% by volume in the film-forming composition, preferably 35 to 60% by volume. If the amount of cycloolefin polymer in the film-forming composition is less than 5% by volume, it becomes difficult to form a desired thickness. In addition, if the amount exceeds 70% by volume, the viscosity becomes too high and the printability deteriorates. If the amount is 35 to 60% by volume, the film-forming composition has appropriate printability.
[0048] Solvent: The solvent dissolves or disperses the cycloolefin polymer, and gives the solute or dispersion a moderate viscosity, so that a mixed composition suitable for the properties of the coating liquid can be achieved. Such solvents can include organic solvents such as hydrocarbons, aromatics, ethers, and ketones. More specifically, pentane, hexane, octane, cyclohexane, methylcyclohexane, ethylcyclohexane, 1,2-dimethylcyclohexane, cyclohexene, benzene, toluene, xylene, ether, tetrahydrofuran, cyclohexanone, methyl ethyl ketone, methyl isobutyl ketone (MIBK), isophorone, etc. can be illustrated. For COP resins or COC resins having polar groups in the molecular chains of cyclocyclic etc., ethyl acetate, butyl acetate, hexyl acetate, dihydropinene acetate, etc. can be used as ester solvents. Solvents with high boiling points are preferred in terms of improving printability.
[0049] The amount of solvent is the remainder other than the cycloolefin polymer and the property modifier, and the approximate amount can be 25 to 90% by volume in the film-forming composition, preferably 35 to 60% by volume. If the amount of solvent in the film-forming composition is less than 25% by volume, the non-volatile component becomes too much and the printability deteriorates. If the amount exceeds 90% by volume, the non-volatile component is too little and it is difficult to form a desired thickness. If the amount is 35 to 60% by volume, the film-forming composition has suitable printability.
[0050] Property adjuster: A property adjuster is a substance that imparts properties to the liquid that cannot be obtained by simply dissolving or dispersing the polymer by being contained in the liquid in which the cycloolefin polymer is dissolved or dispersed. The cycloolefin polymer can be used as a binder resin for coating materials such as printing ink by not only dissolving or dispersing the cycloolefin polymer in a solvent but also adding a property adjuster to the cycloolefin polymer.
[0051] Among the physical property adjusters, as printability improving materials for improving printability, there can be cited viscosity adjusters such as plasticizers for adjusting viscosity, thixotropy imparting agents for imparting thixotropy, foaming inhibitors such as defoaming agents for inhibiting foaming during printing, stringing inhibitors for inhibiting stringing, wettability improvers for preventing shrinkage on the printed substrate and preventing uneven printing and the occurrence of spot patterns, cutting improvers for enabling continuous printing, or coating stabilizers such as silane coupling agents, inhibitors or antioxidants for stabilizing the properties of the film-forming composition.
[0052] Moreover, among the physical property adjusters, as a coating quality improver for improving the coating quality, from the viewpoint of improving the quality of the coating itself, a smoothing agent that improves the surface smoothness when forming a coating can be cited. In addition, from the viewpoint that the coating functions as a protective layer to protect the quality of the conductive part coated inside, a moisture resistance improver that improves moisture resistance, a vulcanization resistance improver that improves vulcanization resistance, a gas barrier improver that inhibits the permeability of gases such as oxygen, a heat resistance improver that improves heat resistance, a light resistance improver that prevents discoloration, an ultraviolet inhibitor that inhibits the transmission of ultraviolet rays, or an adhesion improver that improves adhesion to the substrate sheet can be cited. Among them, moisture resistance improvers, vulcanization resistance improvers, gas barrier improvers, heat resistance improvers, light resistance improvers, or ultraviolet inhibitors from the viewpoint of being a protective layer belong to weather resistance improvers. In addition, they can also be called the names of barrier improvers that express one function.
[0053] As physical property adjusters, petroleum hydrocarbons such as aromatics, paraffins, and cycloalkanes can be cited; or polyolefins such as polyethylene, polypropylene, polybutene, liquid polyisobutylene, liquid polybutene, hydrogenated liquid polyisoprene, and their derivatives; petrolatum, petroleum asphalt, etc. Alternatively, as other physical property adjusters, polyolefins such as maleic anhydride-modified polypropylene that are acid-modified by halogenation or carboxylic acids such as maleic acid can be cited. These substances are printability improvers and also film quality improvers such as weather resistance improvers. One or more of these substances can be used appropriately.
[0054] The physical property adjuster having a polar group such as a hydroxyl group, an amino group, a carbonyl group, a carboxyl group, a nitro group, a sulfonyl group, an ester group, an amide group, a halogen group, etc. is an adhesion improver that helps improve the adhesion of the film-forming composition to the substrate sheet or circuit wiring, etc., which is the object of coating. The physical property adjuster having a reactive functional group such as an epoxy group, a methacrylic group, a vinyl group, a mercapto group, an amino group, etc. helps improve the adhesion of the film-forming composition to the substrate sheet or circuit wiring, etc., which is the object of coating.
[0055] Functional fillers such as titanium oxide and zinc oxide function as coating quality improvers such as moisture resistance improvers that inhibit water vapor permeability, ultraviolet inhibitors that inhibit ultraviolet permeability, vulcanization resistance improvers that inhibit sulfur gas permeability, or gas barrier improvers. In addition, they can also function as printability improvers such as viscosity modifiers, foaming inhibitors, or thixotropy imparting agents.
[0056] The amount of the physical property adjuster is 0.1 to 30% by volume in the film-forming composition, preferably 0.5 to 25% by volume, and more preferably 3 to 20% by volume. The amount of the physical property adjuster is 0.1 to 15% by volume in the film-forming composition, and 3 to 10% by volume is a preferred method. If the amount of the physical property adjuster is less than 0.1% by volume, the printability deteriorates, and if the amount exceeds 30% by volume, the film quality may deteriorate. If the amount is 3 to 20% by volume, it has appropriate printability and can form a film of good quality.
[0057] Modulation of the film-forming composition: The film-forming composition is modulated by dissolving or dispersing the cycloolefin polymer in a solvent, and adding a physical property adjuster and mixing. The viscosity of the obtained film-forming composition measured using a rotational viscometer at a rotation speed of 10 rpm and 25° C. is preferably 1 to 300 Pa·s. If the viscosity of the film-forming composition is less than 1 Pa·s, the shape retention of the patterned circuit wiring may decrease. In addition, if the viscosity exceeds 300 Pa·s, it becomes easy to cause clogging during screen printing, which is a representative coating method, and productivity may be reduced.
[0058] According to the above-mentioned film-forming composition, there is appropriate viscosity and printability relative to the substrate sheet. In addition, when printing or other coatings, the film-forming composition is not easy to produce pinholes, etc., and a smooth film can be formed. In addition, if the film-forming composition solidifies, a high-quality film can be formed as a protective layer.
[0059] Formation of coating: The coating forming composition is applied to a substrate sheet composed of a resin film or the like by screen printing or the like, and is cured to form a coating, which can function as a protective layer of the substrate sheet. According to the characteristics of the cycloolefin polymer, the protective layer can be a highly transparent coating, and the average light transmittance of the protective layer in the visible light range of 400nm to 800nm can be preferably 80% or more, and more preferably 85% or more. In addition to screen printing, the coating method can also use spray coating, coater printing, transfer, dipping, etc.
[0060] The thickness of the coating as a protective layer for protecting the circuit wiring or sensor electrodes can be 0.5 to 50 μm, preferably 3 to 30 μm, and more preferably 6 to 8 μm. The reason is that although the thickness of the coating as a protective layer can be made to exceed 10 μm and formed into a film, it is contrary to the requirement of thin film. In addition, if the thickness of the coating is thinner than 3 μm, the protection of the circuit wiring or sensor electrodes becomes sparse. Moreover, the thickness can be increased by stacking the coating. As a result, the coating can also be thickened to about 100 μm.
[0061] The coating has excellent moisture resistance, light resistance, and sulfur resistance, has low reactivity with respect to chemicals and solvent barrier properties, and the coating itself does not ooze out due to its low volatility. In addition, it has non-migration and non-resin corrosion properties to other components attached to the surface of the coating, and has little contamination to these other components.
[0062] <Circuit Sheet>
[0063] exist Figure 1A The main view and Figure 1B , respectively showing embodiments of protective layers formed of a coating film-forming composition. In the circuit sheet 10 shown in these figures, a coating film-forming composition is applied to cover a conductor 12 provided on a substrate sheet 11 as a protective layer 13, and in these figures, only one conductor 12 forming a circuit is schematically shown. In addition, in the drawings, for the purpose of easily understanding the layer structure, the thickness is shown to be thicker than the lateral width, so the aspect ratio is different from the actual one.
[0064] Substrate sheet: As the substrate sheet 11 of the circuit sheet, a transparent resin film is preferably used. Examples of such resin films include polyethylene terephthalate (PET) resin, polyethylene naphthalate (PEN) resin, polycarbonate (PC) resin, methacrylic acid (PMMA) resin, polypropylene (PP) resin, polyurethane (PU) resin, polyamide (PA) resin, polyethersulfone (PES) resin, polyetheretherketone (PEEK) resin, triacetylcellulose (TAC) resin, cycloolefin polymer (COP), etc. As the substrate sheet 11, a coating composed of a coating forming composition may also be used as the substrate sheet 11. Alternatively, a bottom coating layer, a surface protective layer, or an outer coating layer for the purpose of antistatic etc., which improves the adhesion with the conductor 12 or the protective layer 13, is provided on the substrate sheet 11, or a material that has been surface treated by corona treatment, plasma treatment, ultraviolet irradiation treatment, etc. is used. Preferably, the bottom coating layer is a layer with high adhesion with the substrate sheet. For example, there can be mentioned a coating layer containing a urethane, polyester, acrylic, vinyl acetate, vinyl chloride, styrene-acrylic, acrylic-silicone, styrene-butadiene or other resin, or a coating layer containing an emulsion of these resins.
[0065] Circuit wiring: Figure 1A , 1B In order to facilitate the description of the conductor 12 constituting the circuit wiring, only one conductor 12 is shown. Generally speaking, such a conductor 12 is arranged in a pattern on the substrate sheet 11 to form a circuit (circuit wiring network). As the material of the conductor 12, a conductive paste or conductive ink containing a powder of a highly conductive metal can be exemplified, and the highly conductive metal is copper, aluminum, silver or an alloy containing these metals. Among these metals or alloys, silver wiring mainly using silver is preferred because of its high conductivity and difficulty in oxidation compared to copper. In addition, the conductor 12 can be a wiring using carbon powder such as graphite powder or carbon fiber, carbon black, or a wiring composed of these raw materials mixed with metals.
[0066] Regarding the formation of the circuit wiring, in addition to printing, the circuit wiring can also be formed by providing a conductive portion on the base sheet 11 by metal vapor deposition, and then generating a circuit pattern by etching or the like. In the case of metal vapor deposition, metals such as copper, aluminum, nickel, chromium, zinc, and gold can be used. Among them, copper is preferred because of its low resistance and low cost.
[0067] The circuit sheet 10 is manufactured by printing and forming circuit wiring (conducting wire 12) at a predetermined position on a transparent resin film as a base sheet 11. Then, a coating film forming composition is applied thereon and cured to form a protective layer 13. In this way, the circuit sheet 10 can be obtained. In the case where the cycloolefin polymer or the physical property modifier contains a reactive functional group, it can also react with the base film.
[0068] <Sensor Sheet>
[0069] Figure 2A The main view and Figure 2B The top views of the drawings respectively show other embodiments of the protective layer of the coating film composed of the coating film forming composition. The sensor sheet 20 such as the capacitive sensor sheet shown in these drawings is a sheet in which the coating film forming composition is applied to the conductor 22 and the sensor electrode 24 provided on the base sheet 21 to form the protective layer 13. Among them, for convenience, only one sensor electrode 24 is shown, and the sensor sheet 20 having the circuit wiring and the sensor electrode 24 is described as an example.
[0070] Sensor electrode: The base sheet 21 or the conductor 22 as the base of the sensor sheet 20 is the same as that used in the circuit sheet 10. The sensor electrode 24 can be formed of a conductive paste or conductive ink, a metal vapor-deposited film, etc., which forms circuit wiring, or can be formed of a transparent conductive polymer. If a highly transparent material is used, the sensor position can be illuminated by allowing the backlight to pass through.
[0071] Transparent conductive polymers include polythiophene, polypyrrole, polyaniline, polyparaphenylene, polyacetylene, etc. Specifically, PEDOT / PSS (poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid)) etc. can be exemplified. Transparent conductive polymers can use commercially available coating printing inks. Alternatively, the sensor electrode 24 can also use conductive pastes or conductive inks containing highly transparent materials such as metal nanoparticles such as silver nanoparticles, carbon nanoparticles, or indium tin oxide (ITO) powder in the conductive paste or conductive ink.
[0072] In manufacturing the sensor sheet 20, circuit wiring (conducting wires 22) and sensor electrodes 24 are printed at predetermined positions on a transparent resin film as a base sheet 21. Then, a coating film forming composition is applied thereon, and the solvent is volatilized and cured to form a protective layer 23. In this way, the sensor sheet 20 can be obtained.
[0073] <Sensor sheet (Part 2)>
[0074] Figure 3A The main view and Figure 3BThe top views of the sensor sheets 30 respectively show other embodiments of the sensor sheets 30. The sensor sheets 30 shown in these figures are the same as the sensor sheets 20 described above in that the circuit wiring (conductor 32) and the sensor electrodes 34 on the substrate sheet 31 are covered with a protective layer 33 formed by coating a coating film forming composition. However, the sensor sheet 30 of this embodiment is different in that it is formed into a three-dimensional shape. In addition, the raw materials of each component are the same.
[0075] The sensor sheet 30 can be formed by forming the circuit wiring (conducting wire 32) and the sensor electrode 34 on the flat substrate sheet 31 and then thermally deforming the same as the sensor sheet 20, or by forming the circuit wiring (conducting wire 32) and the sensor electrode 34 on the substrate sheet 31 formed into a three-dimensional shape by printing or vapor deposition. When the substrate sheet 31 is thermally deformed in a later step, it is preferred that the glass transition point Tg of the cycloolefin polymer contained in the coating film forming composition as the protective layer 33 is close to the glass transition point Tg of the substrate sheet 31. This is because the closer the temperature of the glass transition point Tg is, the more the deformation degree of the substrate sheet 31 and the protective layer 33 is the same, and it is less likely to cause distortion, deformation, cracking, etc.
[0076] <Sensor sheet (Part 3)>
[0077] The sensor sheet may be a sheet that is coated with a protective layer after being formed into a three-dimensional shape. The protective layer can be provided by applying a coating film-forming composition to the three-dimensional shape surface using a spray coating method or the like.
[0078] In addition, it is easy for a person skilled in the art to understand that multiple variations that do not substantially exceed the scope and effect of the present invention can be achieved. Therefore, such variations are all included in the scope of the present invention. For example, in the specification or the accompanying drawings, for a term recorded at least once with a different term in a broader sense or synonymous, it is possible to replace it with the different term at any position in the specification or the accompanying drawings. In addition, the composition of the embodiment is not limited to the content described in the embodiment, and various variations can be implemented.
[0079] Example
[0080] <Production of Samples 1 to 12>
[0081] Next, the present invention will be further described based on the examples (comparative examples). A coating-forming composition obtained by mixing the materials shown in the following tables was prepared as samples 1 to 12. In addition, a PET film was used as a substrate sheet, and a conductive film with a thickness of 0.5 μm formed by PEDOT / PSS (trade name; Orgacon EL-P3145, manufactured by AGFA) and a conductive wire with a thickness of 10 μm formed by silver paste (trade name; FA-323, manufactured by Fujikura Chemical Co., Ltd.) were arranged side by side on its surface. Thereafter, any coating-forming composition of samples 1 to 12 was applied to the surface of the substrate sheet having these conductive films and conductive wires with a thickness of 8 μm to prepare a test circuit sheet covering the conductive film and conductive wire. However, at both ends of the conductive film, there were exposed positions (exposed portions) of the conductive film where no coating was provided in order to measure the resistance value. Each of the obtained test circuit sheets was marked with the same sample number as the coated coating-forming composition.
[0082] [Table 1]
[0083]
[0084] [Table 2]
[0085]
[0086] In Table 1, as the types of base polymers, "COC" represents a cycloolefin copolymer (trade name; APL6509T, manufactured by Mitsui Chemicals, Tg 80°C), "COP1" represents a cycloolefin polymer (trade name; Zeonor 1020R, manufactured by Zeon Japan Co., Ltd., Tg 102°C) and a COP resin without a polar group in the ring, "COP2" represents a cycloolefin polymer (trade name; ARTON F4520, manufactured by JSR Corporation, Tg 164°C) and a COP resin containing a polar group in the ring, "acrylic" represents an acrylic resin coating (trade name; ALON S-1017, manufactured by Toagosei Co., Ltd., Tg 95°C), and "urethane" represents a polyurethane resin coating (trade name; TAKELAC WS-5100, manufactured by Mitsui Chemicals, Tg 120°C). In addition, comparing the polarity of COP2, COP1, acrylic acid, and urethane, acrylic acid and urethane have high polarity, and if they are regarded as "high", the polarity of COP2 is medium, and is represented as "medium", and the polarity of COP1 and COC is low, and is represented as "low". In addition, the amount of solvent was finally adjusted so that the total volume of each material of each sample plus the solvent reached 100% by volume, so the "Concentration (volume %)" column of the solvent is represented as "remaining".
[0087] <Various Tests>
[0088] For each of the samples, various tests described below were performed.
[0089] (Printability 1) Viscosity: Since printability is evaluated from the perspective of viscosity, the viscosity of each sample was observed. The results are shown in the "Viscosity" column of Table 1. In Table 1, "A" represents a viscosity within the range where screen printing can be performed without problems. "B" represents a viscosity with a slightly higher viscosity, which makes it difficult to mass-produce, such as being able to perform screen printing but unable to increase the printing speed. "C" represents a viscosity that cannot be printed due to high viscosity.
[0090] (Printability 2) Bubbles: Since the printability is evaluated from the degree of bubble generation in the coating, whether bubbles were generated in the coating of each sample was observed. The results are shown in the "Bubbles" column of Table 1. In Table 1, "A" indicates that no bubbles were generated. "B" indicates that a small amount of bubbles were generated. "C" indicates that a large amount of bubbles were generated.
[0091] (Film quality 1) Transmittance: Since the film quality is evaluated from the transparency of the film, the film-forming composition of each sample was applied to a PET film to form a film with a thickness of 8 to 25 μm. Then, the parallel light transmittance of the film at a wavelength of 200 to 800 nm was measured using a spectrophotometer ("UV-1600PC" manufactured by Shimadzu Corporation).
[0092] (Coating Quality 2) Adhesion: Since the coating quality was evaluated from the viewpoint of adhesion to the substrate sheet, each sample was subjected to an adhesion test. More specifically, a cross cut method was performed based on JIS K5600-5-6 (ISO 2409), and the test results were classified into 6 levels.
[0093] The results are shown in the "Adhesion" column of Table 1. In Table 1, the numbers 0 to 5 are the classifications of the test results obtained by the cross-cut method, 0 means no peeling, and 5 means 35% or more peeling. If it is 0 or 1, it can be considered that the adhesion is good.
[0094] In Table 1, samples 3 and 6 are "2", samples 1, 4, and 5 are "1", sample 2 is "3", and the other samples are "0".
[0095] (Coating Quality 3A) Moisture Resistance A: Since the coating quality is evaluated from the perspective of moisture resistance, the above samples were subjected to a moisture resistance test. More specifically, the test circuit sheet of each sample was placed in an environment of 85% humidity and 85°C for 250 hours, 500 hours, 750 hours, and 1000 hours, and the moisture resistance was evaluated based on the change in the resistance value of the conductive film caused by the transparent conductive polymer after each time. The moisture resistance test observed based on the change in resistance value is referred to as "Moisture Resistance A".
[0096] The resistance value was measured using a resistance meter (tester) from the exposed portions at both ends of the conductive film formed of the transparent conductive polymer.
[0097] As a result, for samples 4, 5, 7, 8, 11, and 12, the resistance value was observed to increase very slowly after 250 hours, and the resistance value after 1000 hours was 1.2 times the resistance value before being placed under the humidity for sample 4, 1.1 times for sample 5, 2.6 times for sample 7, 2.2 times for sample 8, 1.1 times for sample 11, and 1.1 times for sample 12. The COP1 resin was approximately 1.1 to 1.2 times, and the COP2 resin was 1.1 to 2.6 times. On the other hand, the resistance values of sample 9 were 20.0 times, and those of sample 10 were 10.5 times.
[0098] (Coating Quality 3B) Humidity Resistance B: For each sample under the same conditions as the humidity resistance test, unlike the humidity resistance test A in which the resistance value is measured, the color tone of the conductive film of the transparent conductive polymer is observed, and the humidity resistance is evaluated based on the change in color tone. The humidity resistance test observed based on the change in color tone is referred to as "Humidity Resistance B".
[0099] The color change of the conductive film is evaluated as a color difference ΔE based on an index defined as the distance between coordinates in the CIE1976L*a*b* color space, based on JISZ8781-4. The color difference can be obtained using, for example, a handheld spectrophotometer ("JX777" manufactured by COLOR TECHNO SYSTEM Co., Ltd.) or a colorimeter ("CR-400" manufactured by Konica Minolta). For the samples before and after the test, if the color difference ΔE is less than 13, it is difficult to distinguish the color difference by the naked eye, which can be judged as preferred, and if the color difference ΔE is less than 6.5, it can be judged as more preferred.
[0100] In the moisture resistance B test, changes were observed for samples 4 and 5 after 500 hours, and after 1000 hours, the ΔE changes of sample 4 were 3.97, sample 5 was 3.60, sample 7 was 3.00, and sample 8 was 3.00. On the other hand, the ΔE of sample 9 was 15.00, and the ΔE of sample 10 was 7.72. In addition, the ΔE of samples 11 and 12 was 4.00.
[0101] (Coating Quality 4A) Weathering Resistance A: Since the coating quality is evaluated from the perspective of weathering resistance, a thermal cycle test was performed on the test circuit sheets of each sample. More specifically, each test circuit sheet was placed in a constant temperature and humidity chamber with a temperature setting range of -40°C to +85°C, a heating rate of 3°C / min, and a cooling rate of 2°C / min. Then, the weathering resistance was evaluated based on the change in the resistance value of the conductive film of the transparent conductive polymer after 1000 hours. The weathering resistance test observed based on the change in resistance value is referred to as "Weathering Resistance A".
[0102] As a result, the resistance value after the test was 0.9 times the resistance value before the thermal cycle test for Samples 4 and 5, Samples 7 and 8. On the other hand, it was 1.5 times for Sample 9, 2.0 times for Sample 10, and 1.4 times for Samples 11 and 12.
[0103] (Coating Quality 4B) Weather Resistance B: For each sample under the same conditions as the thermal cycle test, unlike the Weather Resistance A test in which the resistance value was measured, the color tone of the conductive film of the transparent conductive polymer was observed, and the weather resistance was evaluated based on the change in color tone. The weather resistance test observed based on the color tone change was referred to as "Weather Resistance B".
[0104] As a result, the ΔE after the test was 1.02 for sample 4, 0.65 for sample 5, 1.10 for sample 7, and 0.80 for sample 8. On the other hand, ΔE was 2.55 for sample 9, 3.00 for sample 10, and 2.00 for samples 11 and 12.
[0105] (Coating quality 5) Sulfurization resistance: Since the coating quality is evaluated from the perspective of sulfurization resistance, a sulfurization resistance test was conducted. More specifically, each test circuit sheet was placed in a closed space containing sulfur powder and placed in a saturated sulfur vapor environment at 85°C for 250 hours. Then, the condition of the silver paste conductor after 250 hours was observed by visual inspection and resistance measurement.
[0106] As a result of the sulfurization resistance test, samples 1, 4, 5, 7, 8, and 10 still had low resistance values and no disconnection. In addition, samples 11 and 12 still had low resistance values and no disconnection. Sample 9 had black spots over the entire width of the lead wire, and the resistance value exceeded 2 MΩ, which could be displayed by the tester, and was evaluated as disconnection.
[0107] <Research>
[0108] Based on the results of the above tests, the following studies were conducted.
[0109] (Printability 1) Viscosity: All samples were rated above "B", and in terms of viscosity, all samples were suitable for screen printing. A careful observation shows that by comparing samples 2 to 5, the printability in terms of viscosity is improved by adding a polyolefin such as liquid polybutene to the COP1 resin, and further adding functional fillers such as titanium oxide or zinc oxide. It can be seen that not only polyolefins such as liquid polybutene, but also functional fillers such as titanium oxide or zinc oxide serve as viscosity adjusters, and can be adjusted to an appropriate viscosity. It can also be seen that the viscosity suitability of COP resin is superior to that of COC resin.
[0110] In addition, according to Samples 11 and 12, the viscosity was evaluated as "A" even though the amount of maleic anhydride-modified polypropylene was increased to 10% by volume and 20% by volume, respectively. Polyolefins such as maleic anhydride-modified polypropylene do not adversely affect printability and can be added at a high concentration.
[0111] (Printability 2) Bubbles: Samples 2 and 6 that do not contain functional fillers such as titanium oxide or zinc oxide have bubbles, which shows that the functional filler acts as a foaming inhibitor and improves the printability. In addition, by comparing Samples 2 and 3, it can be seen that the viscosity and bubbles are improved because they contain polybutene, and polybutene acts as a printability enhancer. Similarly, by comparing Samples 6 and 11, or comparing Samples 6 and 12, it can be seen that the bubbles are improved because they contain polyolefins such as maleic anhydride-modified polypropylene, and such polyolefins act as foaming inhibitors.
[0112] (Film quality 1) Transmittance: Regarding the transmittance at 550nm, the film of sample 3 without filler is 87%, and the film of sample 10 made only of urethane resin is 82%. The transmittance of PET film alone is 89.2%. By comparing the above transmittances, it can be seen that COP resin has a higher transmittance than urethane resin. In addition, the waveform of the transmittance of the film of sample 2, which does not contain a physical property adjuster and is made only of COP resin, is basically the same as the waveform of the transmittance of PET film, which shows that COP resin has a high visible light transmittance close to that of PET resin. By comparing COC resin and COP resin, it can be seen that the value of sample 1 is higher than that of sample 4, and COC resin has a higher transmittance than COP resin.
[0113] On the other hand, comparing the transmittances of samples 6 to 8, the transmittances in the visible light range of 550nm are roughly the same, but in the ultraviolet range of 350nm, it is observed that the transmittances of samples 7 and 8 are lower than that of sample 6. The reason for this result is that since samples 7 and 8 contain functional fillers that are not contained in sample 6, the functional fillers of titanium oxide or zinc oxide reflect ultraviolet rays and do not allow them to pass through. In addition, comparing the transmittances of samples 6, 11, and 12, it is observed that the transmittances of samples 11 and 12 in the visible light range of 550nm are slightly lower than those of sample 6, and the transmittances in the ultraviolet range of 350nm are also lower than those of sample 6. This result is because samples 11 and 12 contain polyolefins such as maleic anhydride-modified polypropylene that are not contained in sample 6, so the polyolefins reflect ultraviolet rays and do not allow them to pass through, and it is known that the polyolefins also function as ultraviolet inhibitors. In addition, by comparing samples 2 and 3, it is known that polybutene also functions as an ultraviolet inhibitor.
[0114] (Coating quality 2) Adhesion: Comparing Sample 2 and Sample 6, Sample 2, which does not contain a physical property adjuster and uses a COP1 resin with low polarity, has poor adhesion, while Sample 6, which does not contain a physical property adjuster but uses a COP2 resin with medium polarity, has slightly improved adhesion. This shows that, from the perspective of adhesion, it is preferable to use a COP resin with medium polarity, i.e., a COP resin with polarity.
[0115] In addition, by comparing Sample 2 and Sample 3 using COP resins of the same polarity, it can be seen that Sample 3 containing polybutene has higher adhesion than Sample 2 not containing polybutene, and polyolefins such as polybutene function as adhesion improvers.
[0116] Furthermore, the adhesion of samples 4 and 5 containing functional fillers is better than that of sample 3 containing no functional filler, which shows that the functional filler also functions as an adhesion enhancer. Comparison of samples 6 to 8 also shows that the adhesion can be greatly improved by containing functional fillers.
[0117] Furthermore, by comparing Sample 6, Sample 11, and Sample 12, it can be seen that the adhesion of the sample to which maleic anhydride-modified polypropylene was added was improved, and that polyolefins other than polybutene also functioned as adhesion improvers.
[0118] (Film quality 3) Moisture resistance: The resistance values of samples 9 and 10 were greatly improved, and ΔE also changed greatly. In contrast, the changes in the resistance values and color tones of samples 4, 5, 7, 8, 11, and 12 were suppressed, which shows that samples 4, 5, 7, 8, 11, and 12 have excellent moisture resistance. From this result, it can be seen that polyolefins such as polybutene and maleic anhydride-modified polypropylene or functional fillers function as moisture resistance improvers and improve the film quality.
[0119] (Film quality 4) Weather resistance: In the weather resistance A test, after the test of 1000 hours, the resistance value of the conductive film of samples 4, 5, 7, and 8 changed by 0.9 times, while that of sample 9 was 1.5 times and that of sample 10 was 2.0 times. In addition, in the weather resistance B test, after the test of 1000 hours, the color tone change ΔE of the conductive film in samples 4, 5, 7, and 8 was 0.65 to 1.10, while that of sample 9 was 2.55 and that of sample 10 was 3.00. Based on this result, it can be seen that the weather resistance of samples 4, 5, 7, and 8 is superior to that of sample 9 or sample 10, and that polyolefins such as polybutene or functional fillers function as weather resistance enhancers to improve the film quality.
[0120] In addition, the resistance value of the conductive film of Sample 11 and Sample 12 in the Weather Resistance A test changed by 1.4 times, and the color tone change ΔE of the conductive film in the Weather Resistance B test was 2.00. From these results, it can be seen that although the weather resistance is not as good as that of Sample 7 or Sample 8, the weather resistance is better than that of Sample 9 or Sample 10, and the maleic anhydride-modified polypropylene also functions as a weather resistance enhancer to improve the coating quality.
[0121] (Film quality 5) Sulfurization resistance: According to the results of the sulfurization resistance test, the sulfurization resistance was improved in samples 4, 5, 7, 8, 11, and 12 without promoting sulfurization. This shows that polyolefins such as polybutene and maleic anhydride-modified polypropylene or functional fillers function as sulfurization resistance enhancers to improve the film quality.
[0122] [Overall]: By comparing sample 2 and sample 3, it can be seen that the addition of polybutene to the COP resin improves the printability and adhesion. It can be seen that although it is somewhat difficult to improve the adhesion, because of the printability, even the COP1 resin with low polarity can form a film from the film-forming composition.
[0123] Similarly, it can be seen from the comparison between Sample 6 and Sample 11 that the addition of maleic anhydride-modified polypropylene to the COP resin improves the printability and adhesion. This shows that even a COP2 resin having low polarity can form a film from the film-forming composition.
[0124] Description of Reference Numerals
[0125] 10 circuit sheets, 20 sensor sheets, 30 sensor sheets.
Claims
1. A coating-forming composition for use as a protective layer on a circuit sheet or a sensor sheet, wherein: Contains cycloolefin polymer, property modifier and solvent, The physical property adjuster is a polyolefin and a functional filler, and the physical property adjuster is used as at least one of a printability improver and a coating quality improver. The printability improver functions as at least one of a stringing inhibitor that suppresses stringing, a wettability improver that prevents shrinkage on the printed substrate to prevent uneven printing and the generation of a spot pattern, and a cutting improver that enables continuous printing. The coating quality improver functions as at least one of a gas barrier improver that suppresses gas permeability, a heat resistance improver that improves heat resistance, a light resistance improver that prevents discoloration, and an ultraviolet inhibitor that suppresses ultraviolet transmission. The functional filler is any one of titanium oxide or zinc oxide. The cycloolefin polymer is formulated in the film-forming composition in an amount of 35 to 60% by volume. The cycloolefin polymer is a COP resin obtained by polymerizing a cycloolefin and is used as a binder resin of a coating material. The COP resin is a cycloolefin-based ring-opening polymer or a hydrogenated product thereof.
2. The film-forming composition according to claim 1, wherein The cycloolefin polymer has a polar group on the ring.
3. The film-forming composition according to claim 1, wherein The film-forming composition contains 0.1 to 30 volume % of the physical property adjuster.
4. The film-forming composition according to claim 1, wherein The polyolefin has a polar group selected from a hydroxyl group, an amino group, a carbonyl group, a carboxyl group, a nitro group, a sulfone group, an ester group, an amide group or a halogen group.
5. The film-forming composition according to any one of claims 1 to 4, wherein The polyolefin has a reactive functional group selected from an epoxy group, a methacrylate group, a vinyl group or a mercapto group.
6. The film-forming composition according to any one of claims 1 to 4, wherein The cycloolefin as a raw material of the cycloolefin polymer is a thermoplastic norbornene-based resin or a thermoplastic tetracyclododecene-based resin.
7. The film-forming composition according to any one of claims 1 to 4, wherein The cycloolefin polymer has any one of the functional groups of a hydroxyl group, an amino group, a carbonyl group, a carboxyl group, a nitro group, a sulfone group, an ester group, and an amide group.
8. The film-forming composition according to any one of claims 1 to 4, wherein The cycloolefin polymer has any one of reactive functional groups of epoxy, methacrylic, vinyl, mercapto, and amino groups.
9. The film-forming composition according to any one of claims 1 to 4, wherein The amount of the solvent added to the film-forming composition is 35 to 60% by volume.
10. The film-forming composition according to any one of claims 1 to 4, wherein The film-forming composition has a viscosity of 1 to 300 Pa·s as measured using a rotational viscometer at a rotational speed of 10 rpm and 25° C.
11. The film-forming composition according to any one of claims 1 to 4, wherein The average light transmittance of the protective layer in the visible light range of 400nm to 800nm is greater than 80%.
12. The film-forming composition according to any one of claims 1 to 4, wherein The thickness of the coating film as the protective layer is 0.5 to 50 μm.
13. The film-forming composition according to claim 1, wherein The polyolefin is polybutene.
14. A coating, wherein: The coating-forming composition is composed of the coating-forming composition according to any one of claims 1 to 13.
15. A circuit sheet, wherein: The invention comprises a base sheet, circuit wiring, and a protective layer composed of the coating-forming composition according to any one of claims 1 to 13.
16. The circuit sheet according to claim 15, wherein: The circuit sheet is in a three-dimensional shape with a curved surface.
17. A sensor sheet, wherein: The invention comprises a base sheet, circuit wiring, sensor electrodes, and a protective layer composed of the coating-forming composition according to any one of claims 1 to 13.
18. The sensor sheet according to claim 17, wherein: The sensor sheet has a three-dimensional shape with a curved surface.
Citation Information
Patent Citations
Coating composition, method for curing said composition, and method for manufacturing barrier film and cured product
CN111566173A
Composition of a thermoplastic norbornene resin containing epoxy groups and its use
DE19509173A1
Thermoplastic norbornane-based resin coating agent and method for forming coating layer
JP2001354896A
Coating material and method for producing the same
JP2007084764A